Influence of social factors, self-esteem, introversion and extroversion on psychological well-being and quality of life among bankers in Ibadan, Osogbo and Akure (2014)
This study examined the influence of psychosocial factors, self esteem, introversion and extroversion on psychological well-being and quality of life among Fidelity bank employees. The study utilized ex-post facto design using random sampling technique to select bankers. Two hundred and forty-four (244) bankers participated in the study yielding a return rate of 94%. The instrument used was closed-ended questionnaire divided into five sections. This comprised of demographic variables, self-esteem, personality factor, quality of life and psychological well-being. Four hypotheses were tested. The result indicated that participants bankers with high self esteem significantly reported higher quality of life and psychological well-being than the those with low self esteem [t(242)=7.01, p<.001 & t(242)=8.32, p<.001J respectively. Also, extrovert bankers significantly reported higher quality of life and psychological well-being than the introvert [t(242)=5.86. p< 001 & t(242)=6.75, p<.001] respectively. The result of the regression analysis indicated that self esteem and introvers ion/extroversion had significant joint influence on quality of life [F(2,242)=18.54; R2=0.225 p<0.001] and psychological well-being [F(2,242)=24.55; R2=0.345 p<0.001]. Also, age, educational status, marital status and job status were significant joint predictors of quality of life F (4,238) = 14.446; R2 = 0.128; p<.001). Based on the findings of the result, it was concluded that selfesteem and personality factor were joint predictors of quality of life and psychological well-being. It was recommended that management of banks should take into consideration these effects and they should develop programs for workers in order to enhance self-esteem and deal with stressful life events